The Effectiveness of Implementing the Teaching Methods of the Hidayatul Mustafid Textbook at Madin Darunnajah Wunut Wonotirto - Farikhin Farikhin; Dr.Muhammad Syakur; Dr. Muh Baehaqi; Ahmad Aji Pangestu (At Turots: Jurnal Pendidikan Islam, 2025)
Learning the science of tajwid is a crucial foundation for maintaining the quality of Qur’anic recitation in a correct and scientifically grounded manner, as emphasized in various classical and contemporary studies on tajwid (Al-Mubarak, 2017). The Hidayatul Mustafid textbook is used as an instructional material for intermediate and advanced levels at Madrasah Diniyah Darunnajah Wunut Wonotirto. However, the effectiveness of the teaching methods applied in this textbook has not been extensively examined, unlike the basic text Hidayatus Sibyan, which has been widely studied (Abdurrozaq, 2022; Salwadani, 2022). This study aims to describe the implementation of learning activities, analyze the effectiveness of the teaching methods used by instructors, and identify supporting factors as well as challenges experienced by students in understanding advanced tajwid material. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results indicate that the analytical-lecture method, musyafahah, drill, and discussion are effective in improving students’ understanding, particularly in advanced topics such as idgham mutaqaribain and mad far‘i, which is also consistent with findings from other research (Mursyidah, 2025). Nevertheless, some students face difficulties in distinguishing certain tajwid rules, requiring more intensive practice. This study recommends strengthening the use of visual media and providing a concise supplementary module for the textbook, following the model of media development that has proven successful for basic-level textbooks (Saadah, 2022)